Exploring the surface morphology of developing wheat starch granules by using Atomic Force Microscopy1. Issue 5 (19th December 2012) - Waduge, Renuka N.; Xu, Song; Bertoft, Eric; Seetharaman, Koushik
Abstract Wheat starch granules from 7, 14, 21, 28, 35, 42, and 49 days after anthesis (DAA) were imaged using AFM. Starches were scanned in their native form as well as following exposure to iodine vapour in‐situ at 100% humidity. Starch at 7 DAA exhibited only one granule population, while starches at other maturities had two size populations. Starches from all stages of maturation exhibited blocklet structures. Larger fuzzy blocklets were observed at early stages while they became smaller and less fuzzy at subsequent stages of maturity. Furthermore, at all stages, small granules had larger fuzzy blocklets and higher surface roughness than the large granule counterpart; however the surface roughness of both small and large granule fractions decreased gradually with maturation. Amorphous growth ring of starch granules with ∼1 × 1 µm to ∼3 × 6 µm size islands were also observed. In‐situ iodine exposure demonstrated that iodine interacted with glucan polymers in the amorphous background first and then spread over to polymers on top of blocklets. Iodine‐glucan polymer interaction further increased the surface roughness.